DEVELOPING A CORAL REEF CONSERVATION MODEL BY INVOLVING LOCAL COMMUNITIES ON SOOP ISLAND, SOUTHWEST PAPUA - Nonon Saribanon; Tatang Mitra Setia; Hariyanto; Njo Fransiscus Xaverius Anditya Ciptadi Putra; Panji B Surata Azis; Yenisbar; Alvira Noer Effendi (Universitas Nasional, 2023)
In the Coral Triangle region, located in Southwest Papua, over 75% of the world's coral reef species are found. Soop Island, a small island in this region, holds significant potential due to its proximity to Sorong City, expansive white sandy beaches, and historical relics such as caves and Japanese bunkers. Nevertheless, the current exploitation of coastal resources is unsustainable. Therefore, a comprehensive and holistic approach through the Social-Ecological System (SES) is essential. Pertamina EP Papua Field, a company operating in the Papua region, has implemented a Coral Reef Conservation Program based on community empowerment. The aim of this study is to identify the potential of coral reefs within the framework of conservation and ecotourism development, involving active community participation on Soop Island. The Coral Reef Conservation Program was initially conducted in 2021 using the Spider Web method. During the 2022-2023 period, in collaboration with the Coral Reef Conservation Community (Terumbu Karang Lestari), the program successfully rehabilitated 1,348 coral reef fragments covering an area of 150 square meters in a relatively short timeframe. Furthermore, these conservation efforts have facilitated sustainable ecotourism development, providing economic opportunities for local residents and supporting the growth of the tourism sector in the region.